Nursing Skills in Handling Earthquakes and the Implications for Nursing Education: A Narrative Review - Setiawan, Deris Riandi; Emaliyawati, Etika; Trisyani, Yanny; Nuraeni, Aan; Noya, Fricilia; Harlasgunawan, Alia Rahmi; Rahman, Luthfi; Sugiharto, Firman (Universitas Padjadjaran, 2025)
Many countries have high earthquake activities. As an integral part of the emergency response team, nurses play a critical role in disaster management. This review aimed to identify nurses' skills in dealing with earthquakes and their implications for the importance of nurse education in this area. This study used a narrative review. The literature was searched using three databases: CINAHL, PubMed, and Scopus, using the keywords